Platform Merdeka Mengajar: Integrasi Teknologi dalam Pendidikan Vokasi dan Pengembangan Guru - Hakim, Muhammad Nur; Abidin, Achmad Anwar (Kharisma: Jurnal Administrasi dan Manajemen Pendidikan, 2024)
This study explores the potential of the Merdeka Mengajar platform in supporting teacher professional development and the integration of technology in vocational education at SMK Negeri 1 Dlanggu Mojokerto, as well as understanding teachers' perceptions and experiences in using the platform. Adopting a qualitative approach, this research investigates how the platform contributes to improving educational quality through the development of teaching skills, collaborative learning, and the use of digital resources. Findings indicate that Merdeka Mengajar facilitates access to a diverse range of learning resources, allowing teachers to enrich teaching content and adopt more interactive and innovative teaching methods, which align with the needs of the modern job market. The study also highlights challenges faced, including difficulties in integrating technology into the existing curriculum and limitations of technological infrastructure. Nonetheless, the overall perception of teachers towards this platform is positive, with many emphasizing its benefits in enhancing student engagement and enriching their learning experiences. This research underscores the importance of ongoing support and technical training for teachers to optimize the use of the platform and suggests better coordination between schools, platform managers, and teachers to overcome existing barriers. In conclusion, the Merdeka Mengajar platform offers significant opportunities to enhance the quality of vocational education through teacher professional development and technology integration. With a holistic and strategic approach, the use of this platform can be more effective, enriching students' learning experiences and preparing them with relevant skills for the future.